Efek Determinasi Terhadap Dividen Kas - Ummi Wahyuni; Subhan, Subhan; Rika Syahadatina (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
Study This aim to know influence profit accounting , profit cash and current cash to dividend cash on company manufacture sector goods consumption listed on the Indonesia Stock Elhange for the 2019-2021 period. Method used in study This is study quantitative. Technique taking sample used is technique purposive sampling. So that sample obtained as many as 30 companies manufacture sector goods consumption listed on the IDX on 2019-2021 years . Technique data collection used in study This use documentation and studies library . Technique data analysis used in study This is test descriptive statistics, test assumption classic, test multiple linear regression, and test hypothesis. Results from study This show that profit accountancy influential positive And significant to dividend cash . Profit cash No influential positive And significant to dividend cash . And results study current cash operation influential positive And significant to dividend cash . Results study profit accounting, profit cash and current cash operation in a manner simultaneous influential to dividend cash. The implications of this research are expected to provide an overview, input, and become material for consideration or evaluation for companies in the consumer goods sector to maximize the distribution of cash dividends to investors.